Acceptance of free-floating car sharing: A decomposed self-efficacy-based value adoption model. Issue 5 (28th May 2022) - Zhu, Ge; Zheng, Jiali; Chen, Yuche
ABSTRACT: Free-floating car sharing (FFCS) service draws attention and has the potential to improve transportation system efficiency and achieve sustainability. This study proposes a self-efficacy-based value adoption model (SVAM) to investigate consumer adoption intention of FFCS by decomposing the perceived value and the self-efficacy. Specifically, the model examines the functional, economical, emotional, and comparative value of FFCS. Additionally, six-dimensional factors are employed to explore consumers' self-efficacy in the context of FFCS. A population-based survey was implemented in Chinese major cities to validate the proposed decomposed SVAM. The results indicated that 66% of respondents intended to adopt FFCS, which may be explained by a combination of perceived value and self-efficacy factors. Moreover, the model explained 79% of the variance in perceived value and 77% of the variance in self-efficacy. Finally, practical implications are provided to better understand value propositions and the formation of users' self-cognition.